Platelet-Rich Plasma Attenuates 30-kDa Fibronectin Fragment–Induced Chemokine and Matrix Metalloproteinase Expression by Meniscocytes and Articular Chondrocytes. (October 2015) - Wang, Chih-Chien; Lee, Chian-Her; Peng, Yi-Jen; Salter, Donald M.; Lee, Herng-Sheng
Background: Proteolytic fragments of fibronectin have catabolic effects on cartilage and menisci. Platelet-rich plasma (PRP) is increasingly being used to treat a range of joint conditions, but it is unknown whether PRP influences fibronectin fragment (FN-f) procatabolic activity. Hypotheses: The procatabolic activity of FN-f on meniscocytes and articular chondrocytes is attenuated by cotreatment with PRP. Study Design: Controlled laboratory study. Methods: Human meniscocytes were treated with FN-f (30 kDa) with or without PRP coincubation, and gene expression was analyzed by complementary DNA microarray analysis. Validation of altered expression of known and novel chemokine and protease genes was undertaken by real-time polymerase chain reaction (RT-PCR) in articular chondrocytes and meniscocytes. Chemokine release was assayed by enzyme-linked immunosorbent assay, and intracellular pathway signaling was evaluated by Western immunoblotting. Results: Microarray analysis and RT-PCR showed increased expression of matrix metalloproteinase ( MMP )1, MMP2, MMP3, MMP9, MMP13, interleukin ( IL )– 6, IL-8 ( CXCL8 ), CCL5, CCL20, and CXCL10 chemokines in meniscocytes after treatment with FN-f. Upregulation of these genes was significantly attenuated by PRP. Similar results were seen with articular chondrocytes, although no changes in MMP2 or MMP9 levels were identified. PRP-induced suppression of gene expression was associated with activation of Akt and p44/p42. Conclusion: PRP treatment attenuates the 30-kDa FN-f–induced expression of a range of proinflammatory chemokines and MMPs, including IL-8, IL-6, CCL20, CCL5, CXCL10, MMP1, MMP3, and MMP13, by both meniscocytes and articular chondrocytes. Clinical Relevance: These observations provide support for the use and further trials of PRP in management of cartilage and meniscal injuries.